Extended Tauberian Theorem for the weighted mean Method of Summability - Çanak, Ï.; Totur, Ü. (Український математичний журнал, 2013)
We prove a new Tauberian-like theorem that establishes the slow oscillation of a real sequence u = (un) on the basis of the weighted mean summability of its generator sequence and some conditions.